Smart aquarium / Hanis Syamimi Harun and Nurul Syahirah Adzahar - Harun, Hanis Syamimi; Syahirah Adzahar, Nurul Syahirah (2015)
This project is design a system of semi-automatic aquarium which includes the care and cleaning of aquarium fish. Fish care system consists of fish feeder, fan, bulb with light sensor and pH sensor. The cleaning system consists of water level sensor, water exchanger, and turbidity sensor. This project was developed on the basis of convenience to the users of the aquarium and small-scale fish farmers. It also stabilizes the water quality in the aquarium besides saving costs, time and manpower. This system uses a PIC 16F877 A microcontroller to control the sensors and have been simulated using the software Proteous. Button and liquid crystal display board (LCD) is used as the input and display all information related to the system. With the advantages of low cost and portable, this system is suitable for small and medium-sized aquarium for fish.